IMPLEMENTASI PERATURAN DAERAH NOMOR 5 TAHUN 2013 TENTANG PENGELOLAAN SAMPAH DI KECAMATAN BARONG TONGKOK KABUPATEN KUTAI BARAT - Dominikus Baping; Dan Buntu Paranoan; Adam Idris (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This research aims to describe, analyze and interpret the implementation of waste management In the District of Barong Tongkok, West Kuta. This study uses a qualitative approach with interview, observation and documentation and then analyzed using an interactive analysis model through a data reduction stage.